Revision of the Family Berberidaceae of India – I - Rao, R. R.; Husain, Tariq; Dutt, Bhaskar; Garg, Arti (Rheedea, 1998)
The genus Berberis with 55 species in India is revised. A key to the Indian species of the genus is provided. For each species the correct binomial. basionym if any, and synonyms, followed by a complete description, phenology, distribution and ecological notes are provided. Specimens examined and the approved acronyms of the names of herbaria where the specimens are deposited are cited. Discussion on nomenclature, wherever necessary, is also provided. The taxonomic and nomenclatural problems related to the complex taxa namely Berberis lycium, B. insignis, B. petiolaris and B. macrosepala have been solved. The present part of the article contains the above details of 35 species. The details of rest of the species will be published in the second part of the article.